2012
DOI: 10.1186/1471-2164-13-629
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq and microarray complement each other in transcriptome profiling

Abstract: BackgroundRNA-seq and microarray are the two popular methods employed for genome-wide transcriptome profiling. Current comparison studies have shown that transcriptome quantified by these two methods correlated well. However, none of them have addressed if they complement each other, considering the strengths and the limitations inherent with them. The pivotal requirement to address this question is the knowledge of a well known data set. In this regard, HrpX regulome from pathogenic bacteria serves as an idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 96 publications
5
97
0
5
Order By: Relevance
“…(Kogenaru et al 2012). O perfil de transcritos superexpressos na condição de Fe -está associado a transoporte celular e proteínas de membrana que são descritos em P. multocida e outras bactérias.…”
Section: Rt-qpcrunclassified
See 1 more Smart Citation
“…(Kogenaru et al 2012). O perfil de transcritos superexpressos na condição de Fe -está associado a transoporte celular e proteínas de membrana que são descritos em P. multocida e outras bactérias.…”
Section: Rt-qpcrunclassified
“…Até recentemente a análise de transcritos expressos por patógenos de interesse médico eram baseados apenas em técnicas de microarray, o que vem sendo complementado e melhorado pelas técnicas de sequenciamento de nova geração (Paustian et al 2001, Paustian et al 2002, Kogenaru et al 2012.…”
Section: Introductionunclassified
“…RNA-seq, however, can detect SNPs and other genetic variations, fusion genes, and levels of different splice variants. It has also been suggested that the two technologies should be used together where possible to detect the maximum coverage of the transcriptome [59]. All data in GEO and ArrayExpress must adhere to "minimum information about a microarray experiments" (MIAME) [60] or "minimum information about sequencing experiments" (MINSEQE) [61]; these are standards dictating that enough information must be included for a second party to sufficiently analyze and/or recreate the experiment.…”
Section: Gene Expressionmentioning
confidence: 99%
“…For more than 10 years, microarrays have been the state-of-the-art for measuring comprehensive expression profiles of genes, although they are now quickly being replaced by NGS technologies, called RNA-Seq [11][12][13]. Both technologies are relatively cost-efficient, require tolerable experimental effort, and allow for measuring the expression of all genes simultaneously.…”
Section: Introductionmentioning
confidence: 99%